PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DISERTAI KOMIK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 PADANG - Putri, Desiana; Aima, Zulfitri; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
Background of this research the interest of students in learning mathematics is still less so the comprehension of mathematics concepts is low in VIII grade and it can be seen from math quiz point in VIII grade at SMPN 5 Padang academic year of 2013/2014. This research aimed to determine whether students comprehension of mathematics concepts by implementing cooperative learning type Numbered Heads Together using Comic better than conventional learning in VIII grade at SMPN5 Padang. This type of research is experimental research using design randomized trials on the subject. The research population was a VIII grade at SMPN 5 Padang academic year of 2013/2014 except class VIII1 and VIII2 because it has a different Minimum Completeness Criteria. Technique sample using randomly, using class VIII3 as experimental class and class VIII5 as control class. The research instrument was a test of comprehension of mathematics concepts using the reliability = 0.78. The data analysis technique used is the one side t test using MINITAB software. Based on the analysis of the data found that the two sample classes are normally distributed and homogeneous at significance level Î± = 0.05. Hypothesis test results obtained P - value = 0.000 is less than Î± , the research hypothesis is accepted. It can be concluded that the students comprehension of mathematics concepts by implementing cooperative learning Type Numbered Heads Together using Comic better than conventional learning in VIII grade at SMPN 5 Padang.